Green Chemistry Applications - Eyvaz, Murat; Yüksel, Ebubekir (IntechOpen, 2019)
Green chemistry is defined as the use of a dozen principles that reduce or eliminate hazardous materials in the design, manufacture, and use of chemical products. Today, it is understood that focusing on precautions to reduce or eliminate existing pollution sources is more effective than looking for a cleaning path after exiting. This book presents the principles of green chemistry for clean production in light of the latest technological developments and increasing environmental awareness. Chapters cover such topics as synthesis and applications of nanomaterials for energy and environmental applications, climate process, alternative green energy sources, and removal of emerging pollutants from water.